Performance of a Toric, Monthly, Soft Contact Lens in Digital Device Users - Pucker AD; Franklin QX; Perkins AF; May K; Kannarr SR; Bromley M; Lievens C (Clinical Optometry)
Andrew D Pucker,1 Quentin X Franklin,2 Amy F Perkins,3 Kristopher May,4 Shane R Kannarr,5 Morgan Bromley,3 Chris Lievens3 1Eminent Ophthalmic Services, Milledgeville, GA, USA; 2Department of Pediatrics, University of Birmingham, Birmingham, AL, USA; 3Research Department, Southern College of Optometry, Memphis, TN, USA; 4Coldwater Vision Center, Coldwater, MS, USA; 5Kannarr Eye Care, Pittsburg, KS, USACorrespondence: Chris Lievens, Southern College of Optometry, 1245 Madison Ave, Memphis, TN, 38104, USA, Tel +1 (901) 722-3330, Email clievens@sco.eduPurpose: To determine the performance of TOTAL30 for Astigmatism (T30fA; Alcon; Fort Worth, TX, USA) contact lenses (CLs) in existing CL wearers who are also frequent digital device users.Methods: This 1-month, 3-visit study recruited adult, 18- to 40-year-old subjects who were required to use daily digital devices for at least 8 hours per day. All subjects were refit into T30fA CLs. A text message visual analog scale (VAS) (± 50 scale; positive being comfortable) evaluate at-home eye comfort across the day at 1 day, 1 week, and 1 month. Subjects were evaluated at 1 month with the Computer Vision Syndrome Questionnaire (CVS-Q), Impact of Dry Eye on Everyday Life (IDEEL) Quality of Life questionnaire, and a custom questionnaire.Results: A total 48 subjects were analyzed (mean age = 28.8 ± 6.3 years; 75% female). At 1 month, IDEEL daily activities, feelings, and work domains scores were 96.7 ± 6.6, 96.4 ± 6.2, and 94.8 ± 8.6, respectively. CVS-Q scores were 3.48 ± 3.73. Most of the subjects indicated that they were satisfied with the overall performance of the study CLs (81.3%) and with their level of eye strain with the study CLs (87.3%). When evaluating CL comfort with the VAS, comfort did not differ across the month at each time point (all p-value ≥ 0.16), yet CL comfort did decrease minimally across the wear day (all p-value < 0.001).Conclusion: These data suggest that the monthly study CLs can provide an excellent wearing experience for those with frequent digital device use.Keywords: contact lens, astigmatism, comfort, digital eye strain, quality of life